PENGARUH SOLVABILITAS; PROFITABILITAS; UKURAN PERUSAHAAN DAN BETA SAHAM TERHADAP NILAI PERUSAHAAN SERTA DAMPAKNYA PADA RETURN SAHAM PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONENNYA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2010-2016 - Mulyana, Bambang; Rini, Rahmatika (Universitas Mercu Buana, 2017)
This study aims to analyze the impact of the Profitability (ROA); Solvability (DER); Firm Size (Size); Beta Stock towards firm value and the impact to stock return. Population in this study uses firm in Automotive Industrial Sub Sectors listed in Indonesian Stock Exchange (IDX) from 2010 until 2016. By using purposive sampling and used regression analysis technique in previously; the data were examined using classical assumption test such as test of normality; heteroscedasticity; multicolinierity; and autocorrelation. The result shows that return on asset; debt to equity ratio and firm size have postitive effect and significant toward price book value; while beta stock have a postitive effect and no significant toward price book value and price to book value have postitive effect and significant toward stock return.